Effects of Microsatellite Instability on the Clinical and Pathological Characteristics of Colon Cancer and the Diagnostic Accuracy of Preoperative Abdominal CT Scans - Rıdvan Yavuz; Orhan Aras; Hüseyin Çiyiltepe; Onur İlkay Dinçer; Ahmet Şükrü Alparslan; Tebessüm Çakır (Diagnostics)
Background: Microsatellite-stable (MSS) and microsatellite-instable (MSI) colon cancer (CC) cases have different characteristics. These characteristics may impact the accuracy of abdominal computed tomography (CT) scan examinations in MSI CC. Methods: A retrospective analysis was conducted to examine the effects of MSI CC on patients’ clinical and tumor characteristics. We determined the accuracy of radiological T and N staging compared to pathological T and N staging in CC patients and evaluated the influence of tumor- and patient-related factors on this accuracy. Results: A total of 131 CC patients who had undergone surgical resection were analyzed. Mismatch repair-deficient (dMMR) CC was predominantly found in the right hemicolon (p = 0.023); it was more likely to exhibit moderate (80.8%) or low-grade differentiation (p = 0.01) and had higher rates of mucinous differentiation (p = 0.001). The median neutrophil and platelet counts and C-reactive protein (CRP) levels at diagnosis were significantly higher in patients with dMMR CC (p = 0.022, p = 0.022, and p = 0.018). The depth of invasion influenced the CRP levels in dMMR CC cases (p = 0.015). The abdominal CT exam was accurate regarding the depth of colonic wall invasion in 58.1% and 38.5% of patients with mismatch repair-proficient (pMMR) and dMMR CC, respectively. The assessment of lymph node invasion was accurate in 44.8% of those with pMMR and 50.0% of those with dMMR CC. There was no significant difference in the accuracy in predicting the T and N statuses between the two groups. The accuracy in the determination of the T and N statuses was not affected by the parameters examined. Conclusions: dMMR CC has specific characteristic features. MSI does not affect the accuracy of preoperative abdominal CT.